HER+ Gender Equality Impact Story Book - CGIAR Initiative on Gender Equality; Cummings, Sarah (CGIAR System Organization, 2024)
The CGIAR Initiative on Gender Equality (HER+) is a CGIAR research initiative working to achieve gender equality and women’s empowerment and boost climate resilience across agrifood systems in Low and Middle Income Countries (LMICs). This story book comprises five stories which highlight the impact of HER+, reflecting just a small part of the multiple initiatives, partnerships, evidence, tools and impact generated by HER+. More information about these can be found here. The first story, Overcoming structural barriers to gender equality and women’s empowerment in agrifood systems, demonstrates how HER+ is addressing structural barriers in collaboration with national governments, national agricultural research and extension systems (NARES), civil society organizations (CSOs), international and national non-governmental organizations (NGOs), UN agencies, and rural men and women. It summarizes the evidence and new tools, guidelines, practices and partnerships which HER+ has developed to address the structural barriers to gender equality in agrifood systems in many LMICs, including in Bangladesh, Egypt, Ethiopia, India, Kenya, Malawi, Mali, Nigeria, and Tanzania. This story also highlights the activities of the four work packages (WPs). Co-design addresses restrictive gender norms in agrifood systems is the second story which explains how WP1 TRANSFORM has developed an innovative guide to identify leverage points and levers to address restrictive gender norms. This guide has now been applied to cassava, poultry and fish value chains in Nigeria and Tanzania. Next, Building capacity and resilience of women farmers in India, illustrates how WP2 EMPOWER is working with Indian government NARES institutions, CSOs, NGOs, and rural women and men to pilot gender-responsive socio-technical innovation bundles (STIBs) in learning labs. This approach strengthens women’s resilience and economic empowerment while addressing gender norms that prevent women from transforming their livestock farming to remunerative businesses. The fourth story, Adoption of sustainable land management interventions in Ethiopia, provides a summary of how HER+ WP3 PROTECT has collaborated with World Vision International and others to integrate co-designed sustainable land management interventions within Ethiopia’s social protection programming, reaching women in poor rural households. Finally, Sustainability systems address gender inequality in value chains from WP4 VOICE shows how HER+ has collaborated with ISEAL Alliance, a global membership organization for sustainability systems, to strengthen capacities to integrate gender equality considerations into Voluntary Sustainability Standards and programming. These efforts support ISEAL members, active in 100+ countries worldwide, to advance gender equality.